A record of volcanic eruptions over the past 2,200 years from Vostok firn cores, central East Antarctica - Veres, Arina N.; Ekaykin, Alexey A.; Golobokova, Liudmila P.; Khodzher, Tamara V.; Khuriganowa, Olga I.; Turkeev, Alexey V. (Frontiers in Earth Science, 2023)
The products of volcanic eruptions found in the snow, firn and ice deposits of the polar ice sheets are precious sources of information on the volcanic forcing of the climate system in the recent or remote past. On the other hand, the layers containing the traces of well-known eruptions serve as absolute age markers that help to construct the depth-age scale for the snow-firn thickness. In this study we present new records of the sulfate concentrations and electrical conductivity (ECM) from three shallow (up to 70 m depth) firn cores drilled in the vicinity of Vostok station (central East Antarctica). In the non-sea-salt sulfate and ECM profiles we were able to identify 68 peaks that can be interpreted as traces of volcanic events. 22 of these peaks can be unambiguously attributed to well-known volcanic eruptions (including Tambora 1816 CE, Huaynaputina 1601 CE, Samalas 1258 CE, Ilopango 541 CE and others), which allowed to construct a robust depth-age scale for the cores. 37 events have their counterparts in other Antarctic cores, but cannot be associated with well-dated eruptions. Finally, 9 peaks do not have analogues in the other cores, i.e. they may be traces of so far unknown volcanic events. According to the newly constructed depth-age function, the deepest studied firn layers (70.20 m) are dated by 192 BCE.